Photonic Jet by a Near‐Unity‐Refractive‐Index Sphere on a Dielectric Substrate with High Index Contrast; Annalen der Physik; Vol. 530, iss. 6 - Yue Liyang; Bing Yan; Monks J. N. James; Dhama R.; Wang Z. Zengbo; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2018, 2018)
Title screen